Women who use violence in intimate relationships: the role of anger, victimization, and symptoms of posttraumatic stress and depression. - Swan, Suzanne C; Gambone, Laura J; Fields, Alice M; Sullivan, Tami P; Snow, David L (Violence and victims, 2005)
The present study examines the role of anger and victimization in women's use of aggression in heterosexual intimate relationships. The sample was composed of 108 women, primarily African American, urban, and poor, who had used violence against a partner in the previous 6 months. Path modeling was used to examine the interrelationships among anger, women's aggressive behavior, victimization, childhood abuse experiences, and symptoms of posttraumatic stress and depression. Results revealed that almost all of the women experienced violence from their partners. Greater frequency of victimization from partners and experiences of childhood abuse increased the likelihood that women would use aggression against their partners. Victimization from partners and childhood abuse also increased the likelihood that women would experience symptoms of posttraumatic stress and depression. Women with more symptoms of posttraumatic stress were also more likely to express anger outwardly towards others. Expressing anger outwardly toward others, in turn, predicted an increased likelihood of using aggression against partners.
Keywords: Adult; Aggression; Anger; Chi-Square Distribution; Depression; Female; Humans; Interpersonal Relations; New England; Questionnaires; Risk Factors; Sexual Partners; Stress Disorders, Post-Traumatic; Stress, Psychological; Women's Health